Forests as protection against airborne immissions - Gode Gravenhorst; Alexander Oltchev; Andrey Sogachev; Andreas Ibrom; Heinrich Kreilein (Meteorologische Zeitschrift, 2005)
The effect of a spruce forest in the Solling-hills (Germany) on the concentration of airborne trace compounds in the atmospheric boundary layer is discussed. The discussion is based on field measurements of vertical concentration profiles and vertical fluxes of reactive trace gases and particles in and above a spruce forest and on numerical modelling. Measured SO2−, O3− and PAN-concentrations are 10 % to 20 % lower near the forest floor than just above the canopy. NO2 is emitted from the forest into the atmospheric boundary layer and NO is transported both from the atmosphere and from the forest floor into the spruce canopy air space. The net NOx−flux between the atmosphere and this spruce forest can be neglected compared quantitatively to other N-fluxes. Numerical experiments using two models show that a 1000 m long spruce forest reduces the near surface concentration of an airborne trace substance with a deposition velocity of about 0.7 cm/s by up to 6 % as compared to the upwind SO2−concentration. If a forest is replaced by a meadow the SO2−concentration at the former downwind side of a forest increases by about 10 %.